Activities, function, and health-related quality of life (HRQOL) of older adults with cancer. Issue 4 (July 2017) - Pergolotti, Mackenzi; Deal, Allison M.; Williams, Grant R.; Bryant, Ashley L.; Bensen, Jeannette T.; Muss, Hyman B.; Reeve, Bryce B.
Abstract: Objective: This study aims to (1) describe the activities, function, and health-related quality of life (HRQOL) of a large sample of older adults (age ≥ 65) with cancer, (2) identify the associations with demographics, cancer type, comorbid conditions, and ability to participate in activities and functional status. Materials and Methods: The Health Registry/Cancer Survivorship Cohort is an institutional database designed to aid cancer survivorship research. The registry includes three measures of patient-reported HRQOL: FACT-G and PROMIS® Global measures for physical and mental health. Other measures included in the registry are cancer type, date from diagnosis, number of comorbid conditions and specific conditions and their limitations in daily activity, and self-reported daily activity/function. Results: Our sample consists of 768 older adults with cancer, mean age 72 years, 60% female, and 90% White. Mean scores for HRQOL: FACT-G (85, range: 25–108), PROMIS-physical (48, range: 16–67) and, PROMIS-mental (51, range: 21–67). In multivariable models, Black race, one or more comorbid conditions, and Gastrointestinal cancer ( p  < .05), and patient- reported decreased levels of activities/function were all independently associated with poor HRQOL ( p  < .0001). Conclusions: Older Black adults with cancer, those that have high comorbidity burden, with gastrointestinal cancers and those that report decreased ability to participate in daily activities/function reported poorer HRQOL. As geriatric oncology moves towards trying to identify who may need supportive services, this study demonstrated that a one question patient-reported level of activities and functional ability were independently associated with physical, mental, and cancer-specific HRQOL.